Understanding psychological distress affecting surgical oncology patients during the COVID-19 pandemic—experience from a tertiary cancer care center in the Middle East - Al-Masri, Mahmoud; Safi, Yasmin; Abou Chaar, Mohamad K.; Al-Najjar, Hani; Shanab, Sobuh Abu; Ammar, Khawlah; Manfalouty, Amani; Aljalabneh, Basim (Frontiers in Psychology, 2025)
BackgroundThe COVID-19 pandemic brought stress and anxiety on a global level, and the rapid growth of cases forced medical facilities to redesign their services, prioritizing urgent surgical care. Cancer centers worldwide continued to function, some at limited capacity. However, many procedures were adapted to avoid unnecessary risks of exposure on staff and patients. Testing have also led to inevitable delays in surgical schedules and placed a burden on vulnerable patients who were already suffering from psychological stress. This study focused on assessing overall psychological distress in cancer patients at King Hussein Cancer Center (KHCC) who required primary curative or debulking surgery and whose operations were rescheduled due to the pandemic.MethodsA cross-sectional study was conducted between 17/April/2020 and 25/May5/2020 using an automated self-administered questionnaire. Distress levels were measured using a tailored scale that combined items from validated instruments (Taylor, HADS, and Zung).ResultsA total of 264 participants completed the questionnaire. Mean age was 54 years (±14.9 years), and genders were equally represented. Breast cancer cases were the most frequent (n = 79, 27.65%). Patients younger than 54 years, regardless of gender (n = 125, 47%), and females in general (n = 140, 53%), scored the highest levels of distress (p < 0.0001, p = 0.018, respectively). Marital status had a positive impact on distress levels (p = 0.008). Central nervous malignancies were associated with higher levels of stress on the multivariate analysis (p = 0.004). Patients who were still experiencing a surgical delay at the time of data collection reported significantly higher distress levels compared to those who had already undergone their delayed or rescheduled surgery (p = 0.001).ConclusionBased on our data, we noticed higher levels of distress in younger individuals (younger than 54 years) and in female participants. The highest levels of distress were recorded in patients awaiting treatment and in those who were diagnosed with central nervous system cancer regardless of their treatment status. Higher levels of stress were reported in COVID-19 specific questions. Our results replicate what was published before in the literature associating the COVID-19 pandemic with stress among cancer patients.